Does Company Size Mediate the Relationship between Leverage and Firm Value in Indonesia Technology Companies? - Muhammad Irfan Aziz; Eriana Kartadjumena (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
This research aims to prove and test the effect of leverage on firm value, with firm size as a moderating variable in technology companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. This study used a quantitative approach with an independent variable on leverage. Dependent variable on firm value and firm size as moderating variable. This study uses convenience sampling with a sample of 32 companies. The data used in this research is secondary data, which is 94 financial reports. The analysis used moderated regression analysis with eViews version 13. The research results show that leverage influences firm value. Firm size weakens the influence of leverage on firm value. This research was developed from previous research by adding firm size as a moderating variable in technology companies listed on the Indonesia Stock Exchange (BEI) for 2019-2022. It proves that investors pay more attention to a company's future growth potential. Large technology companies are considered to have sufficient resources to deal with changes in profitability and the flexibility to adapt to market changes.